2010
DOI: 10.1016/j.ccr.2010.10.032
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Mediates the Establishment and Drug Resistance of MLL Leukemic Stem Cells

Abstract: Identification of molecular pathways essential for cancer stem cells is critical for understanding the underlying biology and designing effective cancer therapeutics. Here, we demonstrated that β-catenin was activated during development of MLL leukemic stem cells (LSCs). Suppression of β-catenin reversed LSCs to a pre-LSC-like stage and significantly reduced the growth of human MLL leukemic cells. Conditional deletion of β-catenin completely abolished the oncogenic potential of MLL-transformed cells. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
231
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(245 citation statements)
references
References 46 publications
7
231
1
Order By: Relevance
“…While there are conflicting data on the role of WNT signaling in normal hematopoietic stem cell self-renewal, mouse models have demonstrated that β-catenin is critical for AML stem cell self-renewal. [2][3][4] These data, combined with the clinical observation that increased canonical WNT signaling in AML blasts at diagnosis is associated with decreased rates of relapse-free and overall survival, suggested a potential clinical benefit for WNT suppression. 5,6 While this approach has shown promise in the treatment of AML, haematologica 2015; 100:e49 questions remain as to which subtypes of AML will benefit.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…While there are conflicting data on the role of WNT signaling in normal hematopoietic stem cell self-renewal, mouse models have demonstrated that β-catenin is critical for AML stem cell self-renewal. [2][3][4] These data, combined with the clinical observation that increased canonical WNT signaling in AML blasts at diagnosis is associated with decreased rates of relapse-free and overall survival, suggested a potential clinical benefit for WNT suppression. 5,6 While this approach has shown promise in the treatment of AML, haematologica 2015; 100:e49 questions remain as to which subtypes of AML will benefit.…”
mentioning
confidence: 95%
“…2,3 It is well known that nuclear translocation of β-catenin in this manner induces target gene transcription through physical interaction with members of the TCF/LEF family of transcription factors. While there are conflicting data on the role of WNT signaling in normal hematopoietic stem cell self-renewal, mouse models have demonstrated that β-catenin is critical for AML stem cell self-renewal.…”
mentioning
confidence: 99%
“…Canonical Wnt signaling is highly activated in cancer stem cells. 9,10 Significant efforts have been made to discover inhibitors for the key effectors of the canonical Wnt signaling pathway. 5 Small-molecule inhibitors of the enzymes Porcupine 11−13 and tankyrase 11,14 have been discovered.…”
mentioning
confidence: 99%
“…To explore the mechanism of B4GALT1 gene action, we studied several signaling pathways which were recognized to be involved in drug resistance process of tumor, such as WNT signaling, Notch pathway, and Hh pathway (26)(27)(28), in K562/ ADR-B4GALT1 shRNA cells. Interestingly, WNT signaling and Notch pathway in K562/ADR cells were not affected by B4GALT1 gene knockdown (data not shown).…”
Section: B4galt1 Gene Silencing Inhibits the Activity Of Hh Signalingmentioning
confidence: 99%